Bridged Aromatic Oxo‐ and Thioethers with Intense Emission in Solution and the Solid State. Issue 16 (6th July 2021) - Riebe, Steffen; Adam, Suliman; Roy, Bibhisan; Maisuls, Iván; Daniliuc, Constantin G.; Dubbert, Justin; Strassert, Cristian A.; Schapiro, Igor; Voskuhl, Jens
Abstract: In this contribution, we report on a class of emitters based on bridged oxo‐ and/or thioethers revealing striking photoluminescence properties in fluid solution and in the solid state. In total, nine compounds were investigated concerning their photophysical properties, which were interpreted by quantum chemical calculations. To our delight, we discovered compounds possessing nearly identical photoluminescence quantum yields ( Φ F ) in solution and in the solid state, which has been rarely reported so far. Besides these efforts, we shed light on the influence of polymorphism and solvent polarity on the emission properties. In addition, an in‐depth X‐ray diffractometric analysis was conducted to correlate molecular packing in the crystal with differences in the photophysical properties. Abstract : A highly emissive system based on bridged aromatic oxo‐ and/or thioethers is implemented . These compounds reveal striking emission properties in the solid state as well as in fluid solutions. Furthermore, solvatochromism as well as polymorphism were observed and the structure‐property relationship within a library of nine different compounds was assessed.